Effect of N-Acetylation Degree on the Properties of Chitosan-Stabilized Pickering Emulsions - WU Jun, SHI Zhaojuan, YUAN Chuanxun, WANG Xingting, JIN Risheng (Shipin Kexue, 2024)
The aim of this study is to apply a modification strategy based on covalently grafting acetyl groups onto polysaccharide chains to improve the emulsifying properties of chitosan. A second aim is to explore the optimal degree of acetylation (DA). Infrared spectroscopy (IR) confirmed that acetic anhydride reacetylation could regulate the DA of chitosan, and substitution only occurred on the amino group at the C2 position. The contact angle results showed that acetylation could effectively improve the non-polar part of chitosan, resulting in enhanced emulsifying properties. The droplet size of the Pickering emulsion stabilized by the modified chitosan significantly decreased compared with that observed with untreated chitosan. The emulsifying activity index (EAI) and emulsion stability index (ESI) of acetylated chitosan with 32% DH were the highest (39.56 m2/g and 65.54 min, respectively), and the average droplet size of the emulsion was the smallest (12.71 µm). In addition, the creaming index (CI) decreased significantly to 11.3% compared with that using untreated chitosan. It is proved that changing the molar proportion of N-acetyl-D-glucosamino units in chitosan can effectively improve the emulsifying properties of chitosan and the storage stability of emulsions.